Identification of a Vinyl Reductase Gene for Chlorophyll Synthesis in Arabidopsis thaliana and Implications for the Evolution of Prochlorococcus Species - Nagata, Nozomi (American Society of Plant Biologists, 2005)
Chlorophyll metabolism has been extensively studied with various organisms, and almost all of the chlorophyll biosynthetic genes have been identified in higher plants. However, only the gene for 3,8-divinyl protochlorophyllide a 8-vinyl reductase (DVR), which is indispensable for monovinyl chlorophyll synthesis, has not been identified yet. In this study, we isolated an Arabidopsis thaliana mutant that accumulated divinyl chlorophyll instead of monovinyl chlorophyll by ethyl methanesulfonate mutagenesis. Map-based cloning of this mutant resulted in the identification of a gene (AT5G18660) that shows sequence similarity with isoflavone reductase genes. The mutant phenotype was complemented by the transformation with the wild-type gene. A recombinant protein encoded by AT5G18660 was expressed in Escherichia coli and found to catalyze the conversion of divinyl chlorophyllide to monovinyl chlorophyllide, thereby demonstrating that the gene encodes a functional DVR. DVR is encoded by a single copy gene in the A. thaliana genome. With the identification of DVR, finally all genes required for chlorophyll biosynthesis have been identified in higher plants. Analysis of the complete genome of A. thaliana showed that it has 15 enzymes encoded by 27 genes for chlorophyll biosynthesis from glutamyl-tRNA(glu) to chlorophyll b. Furthermore, identification of the DVR gene helped understanding the evolution of Prochlorococcus marinus, a marine cyanobacterium that is dominant in the open ocean and is uncommon in using divinyl chlorophylls. A DVR homolog was not found in the genome of P. marinus but found in the Synechococcus sp WH8102 genome, which is consistent with the distribution of divinyl chlorophyll in marine cyanobacteria of the genera Prochlorococcus and Synechococcus.